A geographic mosaic of coevolution between Eurosta solidaginis (Fitch) and its host plant tall goldenrod Solidago altissima (L.). (17th November 2021) - Craig, Timothy P.; Itami, Joanne K.
Abstract: A geographic mosaic of coevolution has produced local reciprocal adaptation in tall goldenrod, Solidago altissima (L.), and the goldenrod ball‐gall fly, Eurosta solidaginis (Fitch 1855). The fly is selected to induce gall diameters that minimize mortality from natural enemies, and the plant is selected to limit gall growth that reduces plant fitness. We conducted a double reciprocal transplant experiment where S. altissima and E. solidaginis from three sites were grown in gardens at each site to partition the gall morphology variation into fly genotype, plant genotype, and the environment components. The host plant gall diameter induced by each E. solidaginis population was adapted to inhibit local natural enemies from ovipositing on or consuming enclosed larvae. Reciprocally, increasing the gall size induced by the local fly population increased the resistance of the local plant host population to gall growth. Differences among sites in natural enemies produced a mosaic of hotspots of coevolutionary arms races between flies selecting for greater gall diameter and plants for smaller diameters, and coldspots where there is no selection on plant or fly for a change in gall diameter. In contrast, the geographic variations of gall length and gall shape were not due to coevolutionary interactions.